Hubungan Antara Kesepian (Loneliness) Dengan Pengungkapan Diri (Self Disclosure) Pada Dewasa Awal Pengguna Media Sosial Instagram - Wulandari, Retno; Gina, Fathana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The researcher's reason is because early adulthood is one of the transition periods from adolescence to adulthood. At that time, there are many feelings that are felt and thoughts in the mind about other people's judgments. Not only that, as explained above, at that time individuals are in the phase of searching for identity and forming broader social relationships. Social media, especially Instagram, is a platform that can facilitate interaction between individuals. However, it also often presents challenges related to social isolation. This phenomenon encourages researchers to explore more about how social media is related to loneliness and the level of self-disclosure that occurs among users, especially in early adulthood. This study was compiled by applying a quantitative approach method. Based on the results of research that has been conducted on 150 early adult respondents who use Instagram social media, it can be concluded that there is a significant positive relationship between loneliness and self-disclosure. This means that the higher the level of loneliness felt by individuals, the higher their tendency to express themselves through social media, especially Instagram.